If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -4) = 2x + 61 Reorder the terms: 5(-4 + x) = 2x + 61 (-4 * 5 + x * 5) = 2x + 61 (-20 + 5x) = 2x + 61 Reorder the terms: -20 + 5x = 61 + 2x Solving -20 + 5x = 61 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -20 + 5x + -2x = 61 + 2x + -2x Combine like terms: 5x + -2x = 3x -20 + 3x = 61 + 2x + -2x Combine like terms: 2x + -2x = 0 -20 + 3x = 61 + 0 -20 + 3x = 61 Add '20' to each side of the equation. -20 + 20 + 3x = 61 + 20 Combine like terms: -20 + 20 = 0 0 + 3x = 61 + 20 3x = 61 + 20 Combine like terms: 61 + 20 = 81 3x = 81 Divide each side by '3'. x = 27 Simplifying x = 27
| 3x+2(1/2x-x)=4 | | 11x+28=4x+224 | | 5x+21-3x+21=6 | | 8p^2-9=11p | | -2x-6+3x=-4 | | -3x+47=-2x+67 | | 15x+12x-123=675+32x | | 2-2x=-4x-4 | | -2y^2-9y=-10 | | 7x-24=-3x+13 | | 7x+7+3x=-63 | | 4x+1=43 | | 0.18(y-6)+0.12y=0.04y-0.03(10) | | x-43=-37 | | 2x+1=-2 | | 5x+10=120-8x | | 3+x+4x=48 | | x+3.2=9.3 | | 4x^3+9x^2-2x+2=0 | | 6=-2x+6x-2 | | 5x-2=x+16# | | 2x+1/12-3x-5/12=5/12 | | 6-7x+6x=2 | | Z^2+3x=10 | | x+3.6=9.7 | | 4=z/9.1 | | 8(c+1)=2(c-2) | | -8=14+x | | 5(3x+9)-5= | | 10+7x+3x=50 | | 2x+39=11+9x | | 75=7x+x+3 |